Practica docente do ensino da matemática :Um estudio de caso no ensino médio no colegío Dom Bosco de Manaus - Barbosa Dos Santos, Edna María (2014)
In the current global information society, the discussion on the Teaching of Mathematics has been observed in various areas of Brazilian society. In this study, the main focus is on the role of Professor of Mathematics in Secondary Education and observations about their work, their knowledge in mathematics and the importance of conveying content with confidence. A new process should be developed together with high school teachers, increasing the ability to communicate in several languages, adquiririndo new knowledge and values, knowing investigate, solve problems and develop, make judgments, assumptions and inferences, develop strategies and procedures , working jointly and cooperatively with continuous learning. Such research is divided into four chapters: the first chapter provides concepts of Teacher Education, the sense of mathematics education, government position, the National Curriculum Standards and the role of public policies on affirmative action. It also presents the concepts of the practice of Mathematics Teaching from the Historical Evolution of the discipline, seeking to understand the difficulties of creation in all stages and analyzing the deficiencies found in the teaching process, indicating the strategies used by instructors, along the history and doing a reflection on learning difficulties currently presented by the students. The second chapter presents the method of inquiry surrounding the concepts of Teacher Training and Teaching Mathematics and its replication in the classes of high school through the Don Bosco College of Teachers, highlighting the impacts perceived by teachers who have at Salesian pedagogy proposal to train competent professionals and citizens committed to a fairer society. The third chapter is reserved for the analysis of data from empirical research, through interviews, observations and document analysis. In the fourth chapter, was organized work on the discussion of the results based on the concepts discussed and the results of the case study, the findings are presented, searching for possible contributions to further reflections on the Practice of Teaching Mathematics.